The MUC5B variant is associated with idiopathic pulmonary fibrosis but not with systemic sclerosis interstitial lung disease in the European Caucasian population. - Raphael Borie (PLoS ONE, 2013)
A polymorphism on the MUC5B promoter (rs35705950) has been associated with idiopathic pulmonary fibrosis (IPF) but not with systemic sclerosis (SSc) with interstitial lung disease (ILD). We genotyped the MUC5B promoter in the first 142 patients of the French national prospective cohort of IPF, in 981 French patients with SSc (346 ILD), 598 Italian patients with SSc (207 ILD), 1383 French controls and 494 Italian controls. A meta-analysis was performed including all American data available. The T risk allele was present in 41.9% of the IPF patients, 10.8% of the controls (P = 2 × 10(-44)), OR 6.3 [4.6-8.7] for heterozygous patients and OR 21.7 [10.4-45.3] for homozygous patients. Prevalence of the T allele was not modified according to age, gender, smoking in IPF patients. However, none of the black patients with IPF presented the T allele. The prevalence of the T risk allele was similar between French (10%) and Italian (12%) cohorts of SSc whatever the presence of an ILD (11.1% and 13.5%, respectively). Meta-analysis confirmed the similarity between French, Italian and American cohorts of IPF or SSc-ILD. This study confirms 1) an association between the T allele risk and IPF, 2) an absence of association with SSc-ILD, suggesting different pathophysiology.